Analisis Ketepatan Deskripsi Konsep pada Buku Teks Kimia Sekolah Menengah Atas kelas XI pada materi Kelarutan dan Hasil Kali Kelarutan - kartika meta metafisika (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This study aims to determine the accuracy of the concept used in Senior High school Chemistry textbooks grade XI that is used in the city of Bogor, especially on solubility concept. The research was conducted by surveying the titles of textbooks used by teachers and students in 10 senior high schools in Bogor city. The three books most widely used by the 10 schools were analyzed for the accuracy of the concept description compared to the content of four university chemistry textbooks on materials related to solubility and solubility products. The results of the analysis were validated by 2 experts. The result of the analysis of three textbooks in circulation indicates the imprecision of concept description and potentially lead to misconception.